Meninjau Aspek Kinerja Sistem Informasi Akuntansi Pada Badan Layanan Umum Daerah (BLUD) Rumah Sakit Umum (RSU) Jampangkulon - Teja Lesmana, Dik Dik; Muchlis, Choifuddin; Purwanti, Rima (Universitas Muhammadiyah Yogyakarta, 2020)
The purpose of this study is to determine the factors that influence the performance of accounting information systems. The factors studied were information technology, top management support and human resource competencies at the Jampang Kulon General Hospital. The research model used is a qualitative method with data collection namely interviews, observation, and documentation. Data analysis techniques used are: 1) data collection, 2) data reduction, 3) data presentation, 4) inference and verification. The results showed that: 1) information technology was strongly supported in processing accounting data at Jampang Kulon Hospital so that the financial statements needed by users could be quickly obtained. 2) The involvement of top management plays a very important role in the development of information systems by providing the resources needed by the facility, so that the performance of the accounting information system produced is of very high quality and the performance of the Hospital will increase. 3) Competence of Human Resources who have the knowledge and skills in using information technology play an important role in supporting the performance of accounting information systems that are produced increasingly better.